Increasing client-side confidence in remote component implementations. - Jagannathan, Ramesh (Software engineering notes.)
When a client makes use of a remote component, it does not have direct access to the remote component's implementation or state information. By observing the component's interactions with its environment, however, the client can determine whether the component's behavior conforms to its promised specification. We present a distributedinfrastructure with which a client can make these observations and thereby increase its confidence in the correctness of the remote component. This infrastructure supports temporal specifications of distributed components with autonomous threads of control. It also supports multiple levels of confidence, with commensurate performance costs. As a proof-of-concept for this design, we have implemented a prototype in Java for distributed systems built using CORBA.